2010
DOI: 10.1007/s12281-010-0035-5
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Biofilms: Relevance in the Setting of Human Disease

Abstract: The use of indwelling medical devices is rapidly growing and is often complicated by infections with biofilm-forming microbes that are resistant to antimicrobial agents and host defense mechanisms. Fungal biofilms have emerged as a clinical problem associated with these medical device infections, causing significant morbidity and mortality. This review discusses the recent advances in the understanding of fungal biofilms, including the role of fungal surface components in adherence, gene expression, and quorum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
53
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 130 publications
(159 reference statements)
0
53
0
1
Order By: Relevance
“…Among fungi, different Candida species are the most common colonizers of implanted medical devices (Kumamoto and Vinces 2005; Ramage et al 2005). Fusarium species and Malessezia pachydermatis also form drug-resistant biofilms on implanted medical devices (Martinez and Fries 2010;Ramage et al 2011). Table 1 describes biofilm characteristics for several fungi commonly associated with device-related biofilm infections.…”
mentioning
confidence: 99%
“…Among fungi, different Candida species are the most common colonizers of implanted medical devices (Kumamoto and Vinces 2005; Ramage et al 2005). Fusarium species and Malessezia pachydermatis also form drug-resistant biofilms on implanted medical devices (Martinez and Fries 2010;Ramage et al 2011). Table 1 describes biofilm characteristics for several fungi commonly associated with device-related biofilm infections.…”
mentioning
confidence: 99%
“…The association in biofilms has a great medical importance as it confers greater resistance to specific mediators of the immune response and increased resistance to antimicrobial agents. This is the main reason why biofilm-associated infections are often refractory to conventional antibiotic therapy (Martinez & Fries, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research in mycology has increasingly focused on biofilm phenotyping (Martinez & Fries, 2010). A wide variety of clinically important fungi have demonstrated the ability to colonize surfaces and form biofilms, including the genera Candida (Ganguly & Mitchell, 2011), Aspergillus (Müller et al, 2011), Coccidioides (Davis et al, 2002), Cryptococcus (Martinez et al, 2008), Pneumocystis (Cushion et al, 2009) and Trichosporon (Di Bonaventura et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that Candida albicans, Cryptococcus neoformans, Aspergillus fumigatus, Pneumocystis spp. and Coccidioides immitis might also be able to produce fungal biofilms in humans (Cannizzo et al, 2007;Martinez and Fries, 2010). Biofilms are extracellular matrices produced by microorganisms (primarily bacteria and fungi) which help the pathogens attach to viable and non-viable surfaces (Van Minnebruggen et al, 2010).…”
mentioning
confidence: 99%
“…Biofilms are extracellular matrices produced by microorganisms (primarily bacteria and fungi) which help the pathogens attach to viable and non-viable surfaces (Van Minnebruggen et al, 2010). Biofilm formation in Candida albicans resulted in a 30-to 2000-fold decrease in sensitivity to certain antifungals including ketoconazole (Martinez and Fries, 2010;Vandeputte et al, 2012). Figueredo et al (2013) reported that M. pachydermatis biofilms exhibited high-level resistance to several antifungals including azoles, at least 3 dilutions higher as compared to planktonic cells.…”
mentioning
confidence: 99%